2011
DOI: 10.1182/blood-2010-10-311936
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer ARC19499 mediates a procoagulant hemostatic effect by inhibiting tissue factor pathway inhibitor

Abstract: Hemophilia A and B are caused by deficiencies in coagulation factor VIII (FVIII) and factor IX, respectively, resulting in deficient blood coagulation via the intrinsic pathway. The extrinsic coagulation pathway, mediated by factor VIIa and tissue factor (TF), remains intact but is negatively regulated by tissue factor pathway inhibitor (TFPI), which inhibits both factor VIIa and its product, factor Xa. This inhibition limits clot initiation via the extrinsic pathway, whereas factor deficiency in hemophilia li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
109
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 44 publications
7
109
1
2
Order By: Relevance
“…More recently, two different kinds of TFPI inhibitors have been investigated: sulfated polysaccharides 16,19 and aptamers. 17,18 Our study, using a strategy to inhibit TFPI that differs from the three previously published methods, confirms the potential interest of this target with regards to restoring blood clotting in hemophilia patients with or without inhibitors.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…More recently, two different kinds of TFPI inhibitors have been investigated: sulfated polysaccharides 16,19 and aptamers. 17,18 Our study, using a strategy to inhibit TFPI that differs from the three previously published methods, confirms the potential interest of this target with regards to restoring blood clotting in hemophilia patients with or without inhibitors.…”
Section: Discussionsupporting
confidence: 73%
“…15 In addition, other approaches to neutralizing TFPI have been shown to be active ex vivo and in animal models. [16][17][18][19] Here, we propose a new approach to unlock the tenase complex of hemophilia patients with or without inhibitor. In contrast to activated factor X (FXa), Gla-domainless FXa (GDXa) is unable to bind to procoagulant phospholipids and is almost completely devoid of procoagulant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The selective production of TFPIα by platelets, compared with the production of TFPIβ by other mouse tissues, suggests that platelet TFPI may have a unique function in the regulation of hemostasis and/or thrombosis. Pharmaceutical agents for treatment of hemophilia that inhibit TFPI are in development (19,20). The data presented here suggest that development of pharmaceutical agents that specifically target platelet TFPI, but not endothelial TFPI, may allow hemostasis at the site of vascular injury in patients with hemophilia while minimizing the potential risk for thrombosis that could result from total intravascular inhibition of TFPI activity.…”
Section: Discussionmentioning
confidence: 90%
“…Additional studies of human plasma clotting assays initiated with dilute TF demonstrated that anti-TFPI antibodies shorten the clotting time of hemophilia plasma more than normal plasma, suggesting that pharmacological inhibitors of TFPI may represent a novel treatment for hemophilia (5,6). Consistent with these in vitro studies, in vivo studies performed in FVIII-deficient rabbits (18), dogs (19), and monkeys (20) have demonstrated that inhibition of TFPI activity reduces injuryinduced blood loss in animal models of hemophilia.…”
mentioning
confidence: 84%
“…Many new and adjunctive therapeutic options have been explored, including platelet infusion, 8 tranexamic acid, 9 ⑀-amino caproic acid, 10 molecules that block tissue factor pathway inhibitor, 11,12 and a combination of phospholipid and fXa 13 and fXIII. 14 Solulin is a recombinant soluble analog of human thrombomodulin.…”
Section: Introductionmentioning
confidence: 99%